RETHINKING 21ST-CENTURY PEDAGOGY: FROM KNOWLEDGE TRANSMISSION TO CULTURAL ENVIRONMENT FORMATION (Education in the 21st Century, 2025)
The modern education system is experiencing an identity crisis caused by a change in civilizational landmarks and the acceleration of socio-cultural processes. Pedagogy formed in the industrial era is unable to adequately respond to the challenges of the 21st century. There is a need to rethink its conceptual foundations: from the functional transmission of knowledge to the formation of a living, cultural and value environment capable of supporting the holistic development of the individual. The article attempts to theoretically substantiate the cultural paradigm of pedagogy as a strategy for the future, in which school becomes not only a place of learning, but also a space for meaning-making and cultural education.Relevance of the article. Traditional models of pedagogy, focused on the transmission of knowledge, are no longer effective in meeting the needs of personal development in the context of globalization and digitalization. This makes it urgent to search for new paradigms that will ensure the holistic development and cultural education of students.The aim of the article is to theoretically substantiate the cultural paradigm of 21st-century pedagogy and propose a practical model of school as a cultural ecosystem that promotes the holistic development of the individual.The objectives of the study are to discover the theoretical foundations of the cultural paradigm of education, to develop a practical model of the school as a cultural ecosystem, to rethink the criteria for assessing educational results taking into account personal and cultural development, and to consider the role of the spiritual dimension in the pedagogical process.       The novelty of the article lies in the substantiation of the cultural paradigm of pedagogy of the 21st century, which combines theoretical foundations (humanistic, cultural-historical and spiritual pedagogy) and a practical model of school as a cultural ecosystem, where the key results of education are not knowledge, but personal dynamics, cultural involvement and spiritual development.Practical significance. The results of the study have high practical significance for the modernization of the educational system in the conditions of the 21st century. The proposed cultural paradigm of pedagogy can be applied: in school practice - when designing educational programs aimed not only at the acquisition of knowledge, but also at the formation of a cultural environment, the development of value orientations, creative thinking and spiritual stability of students; in the organization of school space – when creating a cultural ecosystem, including open educational areas, workshops, cultural halls, which ensures the integration of educational and cultural processes; in the system of assessing educational results – through the introduction of alternative tools (portfolio, project work, self-assessment, pedagogical observation), allowing us to record the personal dynamics and cultural involvement of students; n the socio-cultural policy of the school – through expanding interaction with parents, cultural institutions, representatives of art, science and the local community, which strengthens the role of the school as a cultural center.Thus, the ideas and models proposed in the article can be used both in educational policy and in the practical activities of schools, pedagogical universities and cultural institutions. The implementation of the cultural paradigm contributes to the creation of a holistic educational environment that forms a harmonious personality and sustainable cultural development of society.
Keywords: 21st-century pedagogy; educational ecosystem; school as a community; teacher’s role; personality development; cultural environment; holistic child development; teacher as a cultural architect; socio-cultural education; knowledge transmission